Comparing the efficacy of Dexmedetomidine versus Fentanyl adjuvants in lower limb orthopedic surgeries - Siddiqui, Maqsood Ahmed; Aiman Shah; Muhammad Hassan Raza; Dr Faiza; Shahzad Yaqoob; Faiza Gull (Medical Journal of South Punjab, 2024)
Objective: to compare the effectiveness of dexmedetomidine versus fentanyl as adjuvants to hyperbaric bupivacaine surgeries of lower limb orthopedic. Methods: This randomized controlled trial, approved by the ethics committee Ghulam Muhammad Mahar Medical College, Sukkur, Pakistan, began patient enrollment in May 2023 and concluded in April 2024. The study’s main outcomes were rescue analgesia time and secondary outcomes including total consumption of nalbuphine in twenty-four hours and VAS score at 1, 6, 12, and 24 hours. Results: Rescue analgesia time in dexmedetomidine was greater than fentanyl, 422.44±14.63 minutes and 311.39±7.86, respectively (p<0.001). The average total nalbuphine was lower in Group D as compared to Group F, 7.88±1.84 mg/24 hours and 18.72±2.91 mg/24 hours, respectively (p<0.001). Whereas the frequency of rescue analgesia in Group D was lower than the Group F, 2.22±0.43 /24 hours and 3.72±0.46 /24 hours, respectively (p<0.001). Comparison of VAS score was significant at 6 and at 12 hours, (p<0.001). Conclusion: The study findings indicate that intrathecal administration of dexmedetomidine is a promising alternative to fentanyl as an adjuvant in unilateral spinal anesthesia.